How eating sweets affects the skin – the impact of high glycemic index diet on acne formation: A review - Rękas, Barbara; Stradczuk, Monika; Mazurek, Wojciech; Mazurek, Łukasz; Piętak, Mateusz; Kruczyk, Barbara; Gniot, Marcelina (Journal of Education, Health and Sport, 2024)
Introduction and purpose Acne is one of the most common dermatological conditions, especially in adolescents. The etiology of acne is complex, and many factors influence the formation of lesions. Local inflammation, a proliferation of Propionibacterium acnes, hormonal influences with particular importance of androgens, hyperkeratinization, and excessive sebum production are essential in the pathogenesis. The factors stimulating these processes are complex and not always clear. Therefore, in our work, we focused on investigating the connection between a high-glycemic diet and the formation of acne lesions. The state of knowledge The link between diet and acne has been only mentioned in the literature for many years. However, the development of science has made it possible to understand the exact pathogenesis of acne and the relationship of acne lesions to specific dietary components. Of all the diet products, a high glycemic index diet stands out as the one with the most significant impact. Foods with a high glycemic index, i.e. those with a high amount of simple sugars, through an increase in the expression of factors such as insulin, IGF-1 cause excessive sebum production in the sebaceous glands and even an increase in inflammatory infiltration, which further exacerbates acne lesions. In the following review paper, we have looked at the metabolic pathways and hormonal changes that link the consumption of high glycemic index foods to the formation of acne lesions and described several original papers that unequivocally demonstrate the critical role of this diet on acne formation. Summary Based on the literature, we emphasize that in acne treatment, it is necessary not only to focus on medications but, above all, to look at the patient holistically, modifying the lifestyle with particular importance on modifying the patient's diet by lowering its glycemic index.